Innovative Blended Learning Approaches to Enhance Student Engagement in University - Hidayah Ahmed, Nurul; Andersion, James; Garcíae Martínez, Ana (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
: This study aims to identify and analyze innovative blended teaching strategies to enhance student engagement in Malaysian higher education institutions. By integrating face-to-face and online learning methods, the study emphasizes the application of technology and interactive approaches to foster active student participation in the learning process. The research employs a qualitative approach, utilizing in-depth interviews with lecturers and students alongside observations of teaching practices across several Malaysian higher education institutions. The findings reveal that leveraging digital platforms such as Learning Management Systems (LMS), instructional videos, and project-based learning that combine online and in-person activities can significantly improve student engagement. Students with reliable access to technology and comfort in using online platforms exhibit higher participation in discussions and assignments, whereas those with limited access tend to be less engaged. The study also highlights the critical importance of continuous technology training for lecturers and the provision of equitable resources for students to ensure the success of blended learning initiatives. Consequently, it underscores the necessity of integrating innovative teaching strategies with robust technological support to enhance the quality of education in Malaysian higher education institutions.